Evaluation of Reliability of Rupture and Rotational Strength of the Ceramic Turbine Wheel - Jasim, Haider Hadi (Basrah Journal for Engineering Sciences, 2008)
In this paper, Weibull uni-axial and multi-axial distribution function is applied to evaluate the reliability of the fracture strength of rotating turbine rotor wheel manufactured from ceramic material and have inner surface crack. Three cases are considered, first taking only the effect of rotational stresses, second taking the effect of rotational and thermal stresses in ceramic disc, and third taking the effect of rotational and thermal loading in ceramic blade. It was found that there is a convergence between results gotten from uni-axial and multi-axial distribution function, but multi-axial distribution function give small large in values result compared to uni-axial distribution function. The expected values of rupture strength of ceramic blade is higher than of that of disc material, therefore the failure occurs in blade first than in disc material in service survival.